High Figure‐of‐Merit Gallium Oxide UV Photodetector on Silicon by Molecular Beam Epitaxy: A Path toward Monolithic Integration. Issue 4 (7th February 2021) - Mukhopadhyay, Partha; Hatipoglu, Isa; Sakthivel, Tamil Selvan; Hunter, Daniel A.; Edwards, Paul R.; Martin, Robert W.; Naresh-Kumar, Gunasekar; Seal, Sudipta; Schoenfeld, Winston V.
Abstract : A high figure‐of‐merit UV‐C solar‐blind photodetector (PD) fabricated from thin‐film beta‐gallium oxide (β‐Ga2 O3 ) grown on n ‐Si substrates by plasma‐assisted molecular beam epitaxy is demonstrated. Film growth sequences for nucleation of Ga2 O3 on (100)‐ and (111)‐oriented Si substrates are developed, and the influence of crucial growth parameters is systematically investigated, namely, substrate temperature, oxygen flow rate, and plasma power on the functional properties of the PDs. The PDs show an ultra‐high responsivity of 837 A W −1 and a fast ON/OFF time below 4 ms at −5 V. In addition, they display strong rectifying properties and a sharp cutoff below 280 nm with the average responsivities between 10 and 80 A W −1, a detectivity on the order of 10 10  Jones, and rise/fall times between 4 and 500 ms. High photoconductive gain is likely to be due to the mid‐bandgap donor/acceptor defect levels, including oxygen vacancies in the form of self‐trapped holes. It is demonstrated that these defect levels can be modified by controlling the growth conditions, thereby allowing for tailoring of the PD characteristics for specific applications. The methodology represents a cost‐effective solution over homoepitaxial approaches, with characteristics that meet or exceed those reported previously, offering new possibilities for on‐wafer integration with Si opto‐electronics. Abstract : A high figure‐of‐merit UV‐C photodetector fabricated from thin‐film beta‐gallium oxide on n ‐silicon by molecular beam epitaxy is demonstrated. A developed systematical approach relates growth conditions with material properties, starting from the nucleation layers, and their impact on functional properties of the fabricated photodetectors. The methodology represents a cost‐effective solution over homoepitaxial approaches offering new possibilities for on‐wafer integration with silicon.